Synthesis of 2-(3-methyl-2-oxoquinoxalin-1(2H)-yl)acetamide Based Thiazolidinone Derivatives as Potent Antibacterial and Antifungal Agents - Shiv Kumar; Nitin Kumar; Sushma Drabu; Suroor Ahmed Khan; Ozair Alam; Manav Malhotra; Md. Akram Minhaj (E-Journal of Chemistry)
Twelve compounds belonging to series 2-(3-methyl-2-oxoquinoxalin-1(2H)-yl)-N-[4-oxo-2-(substituted)phenyl-1,3-thiazolidin-3-yl]acetamide (5a-l) were synthesized. These compounds were evaluated for their in-vitro antibacterial against E. coli, S. aureus, K. pneumoniae, P. aeruginosa & antifungal activity against C. albicans, A. niger & A. flavus by cup-plate method. Structures of all the newly synthesized compounds were confirmed by elemental analysis, 1H-NMR & FT-IR spectral data interpretation. Compounds 5d & 5h having p-nitrophenyl & p-trifluoromethylphenyl group respectively on 2-position of thiazolidinone ring attached to N-atom of acetamido group on 1-position of 3-methyl-1H-quinoxaline-2-one, were found to be active against all the bacterial & fungal strains under investigation, while compound 5l having p-chlorophenyl on 2-position of thiazolidinone nucleus was reported as least active compound against all bacterial & fungal strain under investigation.